2021
DOI: 10.1016/j.ijmedinf.2021.104567
|View full text |Cite
|
Sign up to set email alerts
|

Utility and usability of an automated COVID-19 symptom monitoring system (CoSMoS) in primary care during COVID-19 pandemic: A qualitative feasibility study

Abstract: Background COVID-19 telemonitoring applications have been developed and used in primary care to monitor patients quarantined at home. There is a lack of evidence on the utility and usability of telemonitoring applications from end-users’ perspective. Objectives This study aimed to evaluate the feasibility of a COVID-19 symptom monitoring system (CoSMoS) by exploring its utility and usability with end-users. Methods This was a qualitative stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 33 publications
(15 reference statements)
2
22
0
Order By: Relevance
“…Notwithstanding, VERAHs emphasized that they enjoyed the CovidCare management due to the patients' positive feedback and previous experience with the software facilitated the familiarization with it. Considering other prerequisites that enable an easy integration into daily practice and therefore the utilisation of a tool, previous research underscored that it is crucial that monitoring and surveillance data can be integrated into the existing practice management software [7,8,12] , which is in line with our ndings.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Notwithstanding, VERAHs emphasized that they enjoyed the CovidCare management due to the patients' positive feedback and previous experience with the software facilitated the familiarization with it. Considering other prerequisites that enable an easy integration into daily practice and therefore the utilisation of a tool, previous research underscored that it is crucial that monitoring and surveillance data can be integrated into the existing practice management software [7,8,12] , which is in line with our ndings.…”
Section: Discussionsupporting
confidence: 74%
“…Besides, apps, e.g. to support HCP, to collect data on the health status of patients who are selfmanaging [9,10] in home-quarantine have also been developed [11][12][13]. As most COVID-19 patients are treated in general practices, a comprehensive approach is necessary to support them in the management of COVID-19 patients, providing a structured way to detect deterioration, treat patients individually, and reducing uncertainty for both patients and HCP.…”
Section: Introductionmentioning
confidence: 99%
“…During the extraordinary situation of the COVID-19 pandemic, remote telemonitoring has been quickly implemented in different ways [5][6][7][10][11][12][13]. In general, many patients and health care professionals are very positive about this concept.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…The implementation of several home monitoring programs has resulted in a reduction in hospital admissions by allowing for the safe survey of clinical symptoms and vitals [3][4][5][6][7][8][9]. Although many observational studies have studied the effectiveness of home monitoring, few studies have reported on patients' and doctors' experiences with telemonitoring [5,[10][11][12][13]. We focused on the COVID-box experiences of patients and health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…More than half of patients reported in an online survey that they did not have a good experience with a customised “store-and-forward voice and text messaging teleconsultation service” in a low-income and low-resource country [6] . On the other hand, a qualitative study explored the utility and usability of a COVID-19 symptom monitoring system (CoSMoS) with patients and doctors in a middle-income country and found more positive experiences, with doctors preferring to integrate CoSMoS into the electronic medical record [7] . This also reflects the importance of a careful choice of digital health and PCI interventions, implementation strategies and evaluation methodologies [8] .…”
mentioning
confidence: 99%